An investigation into the popularity of Nigerian movies in Zambia: a reception study of Lusaka viewers - Phiri, Diana (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2007)
Motivated by a concern as to why Zambians are attracted to foreign media in the form of Nigerian movies, this thesis is a qualitative audience study which investigates the popularity of Nigerian movies in Zambia with a focus on Lusaka viewers. Against the dominance of Western media and most especially Hollywood movies, this study explores the popularity of Nigerian movies in Zambia which highlights the circulation of media within and between non-Western countries. This is an aspect of trans-national cultural flows that has been ignored in theories of media imperialism. The thesis argues that the widespread popularity of Nigerian movies in Africa and in Zambia in particular necessitates a revision of the conceptions of global cultural flows that privilege the centrality of the West but ignore other centres engaged in contemporary cultural production.
Keywords: Motion pictures, Nigerian; Motion picture audiences -- Zambia